Do Liquidity and Solvency Ratios Matter to Stock Prices in the Transportation Infrastructure Sub-Sector Companies? - Wijaya, Meylynda; Siska, Elmira (ARBITRASE: Journal of Economics and Accounting, 2025)
Stock prices play an important role in reflecting a company's performance in the capital market and are a key consideration for investors before investing. However, the fluctuations in stock prices of Transportation Infrastructure sub sector companies from 2019-2023 raised suspicions of the influence of financial ratios, such as liquidity and solvency ratios. This study aims to determine analysis the effect of liquidity ratio (CR) and solvency ratio (DER) on stock prices of Transportation Infrastructure sub sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. This study uses a quantitative approach in the form of secondary data obtained from the company's financial statements. Sample selection using purposive sampling technique, obtained 6 companies with a total of 30 observation for five years. Data analysis was carried out using SPSS through descriptive statistics, classical assumption test, t-test, and F-tests. The results of the study showed that partially, CR had no significant effect on stock prices with a t-count value of 1.274 < t-table 2.04841 and a significannce of 0.214 > 0.05, while DER had a positive and significant effect with a t-count value of 6.527 > 2.04841 t-table and a significance of 0.000 < 0.05. Simultaneously, CR and DER had a significant effect on stock prices with an F-count value of 30,740 > 3.35 F-table and a significance value of 0.000 < 0.05.